Resolving the Commitment Versus Flexibility Trade-Off: The Role of Resource Accumulation Lags - Pacheco-De-Almeida, Gonçalo; Henderson, James E.; Cool, Karel O. (Academy of Management Journal, 2008)
We examine how time-consuming resource accumulation influences the classic strategy trade-off between commitment and flexibility. In particular, using 1975-95 data from the worldwide petrochemical industry, we study the impact of new plants' time-to-build on firms' decisions to invest under uncertainty. Our results suggest a nontrivial positive effect of resource accumulation lags on investment. Contradicting conventional wisdom, we show that competition may be fiercer in industries in which firms accumulate resources more slowly and that uncertainty is not always a disincentive for investment. The robustness of these results is only diminished for extremely long resource accumulation lags.